2011
DOI: 10.2214/ajr.10.6330
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Masses With Contrast-Enhanced Ultrasound: Initial Experience

Abstract: OBJECTIVE Nearly 25% of solid renal tumors are indolent cancer or benign and can be managed conservatively in selected patients. This prospective study was performed to determine whether preoperative IV microbubble contrast-enhanced ultrasound can be used to differentiate indolent and benign renal tumors from more aggressive clear cell carcinoma. SUBJECTS AND METHODS Thirty-four patients with renal tumors underwent preoperative gray-scale, color, power Doppler, and octafluoropropane microbubble IV contrast-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 28 publications
2
57
0
1
Order By: Relevance
“…The conventional color Doppler US has limitations in resolving intratumor vascularization [13]. Although contrast-enhanced US is an invasive procedure, it has already been successfully applied for measuring tissue perfusion in primary tumor lesions [14] or for monitoring therapy response [15]. …”
Section: Introductionmentioning
confidence: 99%
“…The conventional color Doppler US has limitations in resolving intratumor vascularization [13]. Although contrast-enhanced US is an invasive procedure, it has already been successfully applied for measuring tissue perfusion in primary tumor lesions [14] or for monitoring therapy response [15]. …”
Section: Introductionmentioning
confidence: 99%
“…In previous study with qualitative CEUS analysis, they were reported to be hypo-enhanced throughout the CEUS progress [12]. In our study, their TOC ratio is the lowest compared with ccRCCs and AMLs, which may be attributed to the vascularized stalks of pRCCs, which are characterized by the presence of only small vessels without any enlarged vessels or arteriovenous shunts [11], and to the compact growth pattern of tumor cells in cRCCs [25]. However, there is no significant difference in TOC ratio between these histotypes.…”
Section: Discussionmentioning
confidence: 44%
“…The rich vascular network and alveolar architecture observed on histology renders the strong enhancement seen in ccRCCs [22]. Much effort has gone into quantitative analysis in the differentiation of ccRCC: for instance, Zhang et al [23] reported ccRCC to be the most hyper-enhanced tumor compared with pRCC, cRCC, and AML on CECT, and Gerst et al [11] also reported that the degree of enhancement in ccRCC was significantly higher than that in low-grade malignancy with CEUS. However, these studies enrolled only malignant lesions, or included only a relatively small cohort of benign tumors and those with different modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for 70% of all RCCs, the clear cell subtype is the most common, followed by papillary (10%-15%), chromophobe (5%), unclassified (4%), and other rare subtypes (<1%), including multilocular cystic, collecting duct, medullary, mucinous tubular and spindle cell, neuroblastoma-associated, Xp11.2 translocation-TFE3, and hybrid oncocytic tumor [associated with BirtHogg-Dube´(BHD)] [8-10]. Subtyping has prognostic significance, as clear cell, collecting duct, papillary type 2, and medullary can be aggressive, while papillary type 1, chromophobe, and multilocular cystic are more indolent [8,[10][11][12]. Subtyping can potentially alter management as well; while surgical resection remains the standard of treatment for RCC, in patients who are elderly, have multiple co-morbidities, or are otherwise poor surgical candidates, preoperative knowledge that a tumor is more likely to be a less aggressive RCC subtype may lead to consideration of ablation therapy or surveillance, rather than surgery.…”
mentioning
confidence: 99%